A high-bonding concrete and its processing technology

By using a variety of raw materials and modification processes, the existing high-bonding concrete has been solved, and the problems of poor mechanical properties, insufficient bonding properties and unsatisfactory peeling resistance are achieved, and concrete materials with high bonding, strength and durability are suitable for A wide range of application scenarios.

CN116874228BActive Publication Date: 2025-02-18JIANGXI TIANHE CONSTR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310842673.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-02-18
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

The existing high-bonding concrete has problems such as poor mechanical properties, insufficient bonding properties, and unsatisfactory peeling resistance.

Method used

Using basalt coarse, fine aggregate, blast furnace slag powder, modified filler, modified asphalt and reinforced fiber, the bonding performance and compressive strength of concrete are improved through the preparation method of modified asphalt and modified filler, and The production process is simplified through low-temperature stirring and mixing, high-temperature hot mixing and other processes.

Benefits of technology

It significantly improves the compactness, durability, compressive strength, crack resistance and peeling resistance of concrete, and is suitable for concrete structures in various construction and transportation fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004331172050000071
    Figure BDA0004331172050000071
Patent Text Reader

Abstract

The present invention discloses a high-bonding concrete and a processing technology thereof, comprising the following components: aggregate, blast furnace slag powder, lime, modified filler, modified asphalt, and reinforcing fiber. Compared with the prior art, the high-bonding concrete prepared by the present invention improves the compactness and durability of the concrete, enhances the compressive strength, crack resistance and durability of the concrete, has a simple processing technology, is easy to operate, can reduce production costs, is applicable to concrete structures in various fields such as construction and transportation, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a high-adhesion concrete and a processing technology thereof. Background Art

[0002] High-cohesion concrete is a new type of concrete material. The current existing technologies mainly include silicate cementitious materials. Using silicate cementitious materials as gelling agents and adding appropriate amounts of ultrafine mineral powders and chemical admixtures can improve the cohesion and strength of concrete. High-performance concrete uses high-performance cementitious materials, appropriate amounts of ultrafine mineral powders and chemical admixtures to improve the compressive strength, crack resistance and durability of concrete. Self-compacting concrete uses special admixtures and production processes to form microscopic bubbles inside the concrete, thereby improving the compactness and durability of the concrete. Nanomaterial-reinforced concrete uses nanomaterials as reinforcing agents to improve the strength and durability of concrete. Modified asphalt concrete uses modified asphalt instead of traditional cement as a gelling agent to improve the cohesion and durability of concrete.

[0003] There is a balance problem between adhesion and strength in modified asphalt concrete. Modified asphalt concrete improves adhesion by adding modifiers, but it will also affect the strength and durability of concrete to a certain extent. It is necessary to strike a balance between adhesion and strength.

[0004] Therefore, when preparing high-bonding concrete, it is necessary to comprehensively consider its advantages and disadvantages and select appropriate materials and production processes to meet specific application scenarios and performance requirements.

[0005] The invention patent CN111807781B discloses a high-bonding fiber-reinforced concrete and its processing technology, including the following weight components: 100-120 parts of cement, 4-6 parts of fiber, 420-480 parts of aggregate, and 35-50 parts of water. The invention improves the strength of concrete with fiber as the main component and improves the bonding of concrete with cement as the main component through the setting of components and processes in concrete, the role of single components and single processes, and the coordination between multiple components and multiple processes, and is suitable for wide promotion and use. However, the high-bonding fiber-reinforced concrete prepared by the invention has the disadvantages of poor mechanical properties, insufficient bonding, and unsatisfactory anti-stripping. Summary of the invention

[0006] In view of the fact that high-bonding concrete in the prior art has the disadvantages of poor mechanical properties, insufficient adhesion and unsatisfactory anti-stripping, the technical problem to be solved by the present invention is to provide a concrete with high bonding, good mechanical properties and anti-stripping effect and its processing technology.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] A high-bonding concrete comprises the following components: aggregate, blast furnace slag powder, lime, modified filler, modified asphalt and reinforcing fiber.

[0009] Preferably, the high-adhesion concrete comprises the following components in parts by weight: 80 to 120 parts of aggregate, 15 to 25 parts of blast furnace slag powder, 10 to 15 parts of lime, 15 to 25 parts of modified filler, 60 to 100 parts of modified asphalt, and 3 to 5 parts of reinforcing fiber.

[0010] The aggregate is a mixture of basalt coarse aggregate and basalt fine aggregate in a ratio of 0.5-2:0.5-2.

[0011] The particle size of the basalt coarse aggregate is 5 to 30 mm; the particle size of the basalt fine aggregate is 0.5 to 2 mm.

[0012] The reinforcing fiber is at least one of basalt fiber, glass fiber, carbon fiber, polypropylene fiber, polyester fiber, polyethylene fiber, and polyacrylamide fiber.

[0013] The preparation method of the modified asphalt is as follows, in parts by weight:

[0014] Heat 15 to 25 parts of asphalt to 160 to 180°C, add maleic anhydride grafted EVA particles with a mass fraction of 5 to 10% of the asphalt and mineral oil with a mass fraction of 1 to 3% of the asphalt, carry out low-speed shear swelling at a shear rate of 1500 to 3000 r / min for 10 to 30 minutes, and then carry out high-speed shearing at a shear rate of 3000 to 5000 r / min for 40 to 80 minutes to obtain modified asphalt.

[0015] The preparation method of the modified filler is as follows, in parts by weight:

[0016] S1. Add 0.5 to 2 parts of tris(3-triethoxysilylpropyl)triisocyanate to 8 to 12 parts of diethylene glycol ethyl ether at 70 to 90° C. and 100 to 300 rpm, and continue stirring for 5 to 20 hours to obtain a modifier;

[0017] S2, adding 15-25 parts of silicon powder to 80-120 parts of the mixed solution, stirring at 60-80° C. and 100-300 rpm for 5-15 min, then ultrasonicating at 100-300 W for 5-15 min and an ultrasonic frequency of 40-100 kHz to obtain a dispersion, adding 8-12 parts of the modifier prepared in step S1, stirring at 100-300 rpm for reaction for 8-15 h, and drying at 60-80° C. under a nitrogen flow until all the solvents evaporate to obtain a modified filler.

[0018] Preferably, the mixed solution in step S2 is prepared by mixing anhydrous ethanol: water: ammonia monohydrate in a weight ratio of 4-6: 0.5-2: 0.5-2.

[0019] The processing technology of the high-bonding concrete is as follows:

[0020] Step 1, weighing each raw material according to weight, stirring and mixing basalt coarse aggregate, basalt fine aggregate, and blast furnace slag powder at 10-20 rpm for 30-50 minutes, and drying at 25-40° C. during the stirring and mixing process to obtain a mixture;

[0021] Step 2: Put the mixture prepared in step 1 into a mixing tank, heat the modified asphalt to 150-180° C., add it evenly into the mixing tank within 20-30 seconds, stir for 1-3 hours at a stirring speed of 15-25 rpm, and obtain an asphalt mixture;

[0022] Step 3, preheat the asphalt mixture prepared in step 2 and add it to the above-mentioned mixing tank together with basalt fiber, maintain the temperature in the mixing tank at 150-180°C, stir at a speed of 15-25rpm for 20-40min, then add lime and modified filler, stir and mix at a speed of 20-40rpm for 10-30min, control the discharge temperature at 160-170°C, and obtain high-adhesion concrete.

[0023] Ordinary silicon powder cannot be well dispersed in asphalt, and it is easy to form structural defects, which affects the mechanical properties of concrete. In the present invention, the dispersibility of silicon powder in asphalt is enhanced by grafting polymers on the surface of silicon powder. And the prepared modified filler can produce a denser matrix through the filler effect, fill the defects of concrete, and have higher compressive strength. The modified filler can also react with the matrix and produce a more uniform matrix. Improve the structural defects of concrete. On the other hand, the structural strength of concrete depends on the extrusion force between aggregates and the bonding force between aggregates and cement. The present invention modifies asphalt. The main principle is to use the shearing action of the rotor and stator in the high-speed shearing machine to process maleic anhydride grafted EVA particles and mineral oil into fine particles and evenly disperse them in asphalt. Improve the cohesion between asphalt and aggregate. And the added mineral oil can promote the hardening of asphalt and improve its deformation resistance.

[0024] The addition of modified fillers increases its strength, but the modified fillers also reduce the fluidity of the mortar. The present invention selects a suitable amount of modified fillers, which can not only have a positive impact on the strength of the concrete, but also meet the fluidity requirements and can penetrate into the modified asphalt.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) The high-bonding concrete prepared by the present invention uses a variety of raw materials such as basalt coarse and fine aggregates and blast furnace slag powder, which can improve the compactness and durability of concrete and enhance the compressive strength, crack resistance and durability of concrete.

[0027] 2) The present invention adopts various functional agents such as modified asphalt, modified filler and reinforcing fiber, which can improve the bonding performance of concrete and enhance the shear and compressive strength of concrete.

[0028] 3) The production process of the present invention is simple, and adopts low-temperature stirring and mixing, high-temperature hot mixing and other processes. The production process is simple and easy to operate, which can reduce production costs.

[0029] 4) The high-bonding concrete prepared by the present invention is suitable for concrete structures in various fields such as construction and transportation, and has broad application prospects. DETAILED DESCRIPTION

[0030] Main sources of substances:

[0031] Basalt coarse aggregate: particle size: 10-20mm.

[0032] Basalt fine aggregate: particle size: 1~2mm.

[0033] Blast furnace slag powder: Lingshou County Suda Mineral Products Processing Plant, item number: K-02.

[0034] Asphalt: Anhui Boyu New Materials Co., Ltd., model: BY-20.

[0035] Maleic anhydride grafted EVA particles: Dongguan Taotao Plastic Raw Materials Co., Ltd., brand: 30E671.

[0036] Mineral oil: Jinan Xinhuihuang Chemical Co., Ltd., model: 10#.

[0037] Basalt fiber: Taian Haoda New Materials Co., Ltd., length: 5-50 mm, diameter: 13-17 μm.

[0038] Silica powder: particle size: 1250 mesh.

[0039] Example 1

[0040] A processing technology of high-bonding concrete is as follows:

[0041] Step 1, 50 kg of basalt coarse aggregate, 50 kg of basalt fine aggregate, and 20 kg of blast furnace slag powder were stirred and mixed at 15 rpm for 40 min, and dried at 30° C. during the stirring and mixing process to obtain a mixture;

[0042] Step 2: put the mixture prepared in step 1 into a mixing tank, heat 80 kg of modified asphalt to 160° C., add it evenly into the mixing tank within 25 seconds, stir for 2 hours at a stirring speed of 20 rpm, and obtain an asphalt mixture;

[0043] Step 3: Preheat the asphalt mixture prepared in step 2 and add it to the above-mentioned mixing tank together with 4 kg of basalt fiber. Maintain the temperature in the mixing tank at 170°C and stir at a speed of 20 rpm for 30 min. Then add 12 kg of lime and 20 kg of modified filler and stir and mix at a speed of 30 rpm for 15 min. Control the discharge temperature at 165°C to obtain high-adhesion concrete.

[0044] The preparation method of the modified asphalt is as follows:

[0045] Heat 20 kg of asphalt to 170°C, add maleic anhydride grafted EVA particles with a mass fraction of 8% of asphalt and mineral oil with a mass fraction of asphalt 2%, perform low-speed shear swelling at a shear rate of 2000 r / min for 20 minutes, and then perform high-speed shear at a shear rate of 4000 r / min for 60 minutes to obtain modified asphalt.

[0046] The preparation method of the modified filler is as follows:

[0047] S1. Add 1 kg of tris(3-triethoxysilylpropyl)isocyanate to 10 kg of diethylene glycol ethyl ether at 80° C. and 200 rpm under stirring, and continue stirring for 12 hours to obtain a modifier;

[0048] S2. Add 20 kg of silicon powder to 100 kg of a mixed solution, wherein the mixed solution is prepared by mixing anhydrous ethanol, water and ammonia monohydrate in a weight ratio of 5:1:1, stir at 70°C and 200 rpm for 10 min, then ultrasonicate at 200 W for 10 min with an ultrasonic frequency of 60 kHz to obtain a dispersion, add 10 kg of the modifier prepared in step S1, stir at 200 rpm for 12 h, and dry at 70°C under a nitrogen flow until all the solvent evaporates to obtain a modified filler.

[0049] Example 2

[0050] The method for preparing a high-adhesion concrete is basically the same as that in Example 1, with the only difference being that the modified asphalt is replaced with an equal amount of asphalt.

[0051] The preparation method of the modified filler is the same as that of Example 1.

[0052] Example 3

[0053] The method for preparing a high-bonding concrete is substantially the same as that of Example 1, with the only difference being that the modified filler is replaced with an equal amount of silica powder.

[0054] The preparation method of the modified asphalt is the same as that in Example 1.

[0055] Comparative Example 1

[0056] A method for preparing high-cohesion concrete is substantially the same as that of Example 1, with the only difference being that no modified filler is added in the method for preparing the high-cohesion concrete.

[0057] The preparation method of the modified asphalt is the same as that in Example 1.

[0058] Test Example 1

[0059] Mechanical properties test

[0060] The axial compressive strength, compressive strain and axial compression deformation modulus of asphalt concrete are obtained through compression tests. The compression test of the present invention is carried out on 3 specimens for each mix ratio in the embodiment and the comparative example, and the test results are average values. The test steps are as follows:

[0061] (1) The compression test piece is formed by compacting the high-bonding concrete prepared by the present invention using a standard Marshall compactor. The specific method is to compact the concrete layer by layer every 50 mm in a Φ100 mm molding mold, and compact each layer 35 times. After the last layer is compacted, the mold is turned over and compacted 35 times. The size of the compression test piece is a cylindrical test piece of Φ100×100 mm.

[0062] (2) Use a caliper to measure the size of the specimen. The error between the measured size of the specimen and the size specified during design, i.e. the specified size, cannot be greater than 1 mm. The size measurement of the specimen must be accurate to 0.1 mm.

[0063] (3) After the specimen has been placed at room temperature for 24 hours, it is placed in a constant temperature water bath at the test temperature (i.e. 22.4°C) for a constant temperature time of not less than 4 hours.

[0064] (4) Take out the specimen that has been heated to the test temperature and install it on the tester so that the axis of the specimen coincides with the center of the base plate. After the specimen is installed, the test can be started with a strain rate of 1.0 mm / min (i.e., a strain rate of 1% / min). The test is stopped when the specimen is completely destroyed. The test data is collected on the computer through the acquisition system.

[0065] The compressive strength (accurate to 0.01MPa) and compression strain calculation formula of the specimen are as follows:

[0066] Rc=P / A

[0067] ε=δ / h×100%

[0068] Where:

[0069] Rc——compressive strength, MPa;

[0070] ε——strain of the specimen at maximum stress, %;

[0071] P——maximum load of the specimen under compression, N;

[0072] A——pressure area of ​​the specimen, mm 2 ;

[0073] h——test piece height, mm;

[0074] δ——vertical deformation at maximum load, mm;

[0075] The test results are shown in Table 1.

[0076] Table 1: Mechanical properties test results

[0077]

[0078] Test Example 2

[0079] Anti-peeling performance test

[0080] Rutting plate specimen molding: The high-bonding concrete prepared by the present invention is molded into a rutting plate with a standard size of 300 mm×300 mm×50 mm by a wheel rolling method, and the surface of the rutting plate specimen is ensured to be flat;

[0081] Water bath pretreatment: After the formed rutting board is cured at room temperature for at least 12 hours, it is pretreated in a water bath, wherein the water bath time is 24 hours and the water bath temperature is 20°C;

[0082] High temperature wheel rolling: The rutting plate specimens that have been pretreated in different water baths are placed in a rutting test machine, and the temperature is set to 60°C, the wheel load pressure is set to 0.8MPa, and the wheel rolling test time is 60min.

[0083] Drilling core samples: Use a core drill to drill core samples under the wheel track after the high temperature wheel track test. Drill two core samples from each wheel track plate specimen. The core sample diameter is 100mm.

[0084] Scattering test: Weigh the mass m0 of the drilled core sample and place it in a scattering test abrasion machine for a scattering test. During the test, record the mass m1 after 500 revolutions and calculate the aggregate spalling mass loss according to the following formula:

[0085] ΔS=(m0-m1) / m0×100%

[0086] Where: ΔS—mass loss of asphalt concrete (%);

[0087] m0—mass of asphalt concrete specimen before the test (g);

[0088] M1—The mass of the asphalt concrete specimen after the test rotation number is 500 revolutions (g).

[0089] Each group was tested three times and the average value was taken. The test results are shown in Table 2.

[0090] Table 2: Anti-peeling performance test results

[0091] Trial plan Mass loss (%) Example 1 12.5 Example 2 14.6 Example 3 14.4 Comparative Example 1 16.4

[0092] It can be seen from the test results of test examples 1 to 2 that the mechanical and anti-stripping properties of Example 1 are the best. The possible reason is that in Example 1 of the present invention, basalt coarse aggregate, basalt fine aggregate, and blast furnace slag powder are stirred and mixed, and dried to obtain a mixture; modified asphalt is added and heated to 160°C, and stirred to obtain an asphalt mixture; basalt fiber is added, the temperature is maintained at 170°C, and stirred, and then lime and modified filler are added and stirred to obtain high-cohesive concrete. The modified asphalt is obtained by heating asphalt, adding maleic anhydride grafted EVA particles and mineral oil, shearing and swelling at a low speed, and then shearing at a high speed. The modified filler is prepared by adding tris(3-triethoxysilylpropyl)triisocyanate to diethylene glycol ethyl ether under high temperature stirring, and continuing to stir to obtain a modifier; adding silicon powder to a mixed solution, wherein the mixed solution is prepared by anhydrous ethanol: water: monohydrated ammonia, stirring, and then ultrasonicating to obtain a dispersion, adding a modifier, stirring to react, and drying until all the solvents evaporate to obtain a modified filler.

[0093] Ordinary silicon powder cannot be well dispersed in asphalt, and it is easy to form structural defects, which affects the mechanical properties of concrete. In the present invention, the dispersibility of silicon powder in asphalt is enhanced by grafting polymers on the surface of silicon powder. And the prepared modified filler can produce a denser matrix through the filler effect, fill the defects of concrete, and have higher compressive strength. The modified filler can also react with the matrix and produce a more uniform matrix. Improve the structural defects of concrete. On the other hand, the structural strength of concrete depends on the extrusion force between aggregates and the bonding force between aggregates and cement. The present invention modifies asphalt. The main principle is to use the shearing action of the rotor and stator in the high-speed shearing machine to process maleic anhydride grafted EVA particles and mineral oil into fine particles and evenly disperse them in asphalt. Improve the cohesion between asphalt and aggregate. And the added mineral oil can promote the hardening of asphalt and improve its deformation resistance.

[0094] The addition of modified fillers increases its strength, but the modified fillers also reduce the fluidity of the mortar. The present invention selects a suitable amount of modified fillers, which can not only have a positive impact on the strength of the concrete, but also meet the fluidity requirements and can penetrate into the modified asphalt.

Claims

1. A high-bonding concrete, characterized in that: The invention comprises the following components by weight: 80 to 120 parts of aggregate, 15 to 25 parts of blast furnace slag powder, 10 to 15 parts of lime, 15 to 25 parts of modified filler, 60 to 100 parts of modified asphalt, and 3 to 5 parts of reinforcing fiber; The preparation method of the modified asphalt is as follows, in parts by weight: Heat 15 to 25 parts of asphalt to 160 to 180° C., add maleic anhydride grafted EVA particles with a mass fraction of 5 to 10% of asphalt and mineral oil with a mass fraction of 1 to 3% of asphalt, perform low-speed shear swelling at a shear rate of 1500 to 3000 r / min for 10 to 30 minutes, and then perform high-speed shearing at a shear rate of 3000 to 5000 r / min for 40 to 80 minutes to obtain modified asphalt; The preparation method of the modified filler is as follows, in parts by weight: S1. Add 0.5 to 2 parts of tris(3-triethoxysilylpropyl)triisocyanate to 8 to 12 parts of diethylene glycol ethyl ether at 70 to 90° C. and 100 to 300 rpm, and continue stirring for 5 to 20 hours to obtain a modifier; S2, adding 15-25 parts of silicon powder to 80-120 parts of the mixed solution, stirring at 60-80°C and 100-300 rpm for 5-15 min, then ultrasonicating at 100-300 W for 5-15 min and an ultrasonic frequency of 40-100 kHz to obtain a dispersion, adding 8-12 parts of the modifier prepared in step S1, stirring at 100-300 rpm for 8-15 h, and drying at 60-80°C under a nitrogen flow until all the solvent evaporates to obtain a modified filler; The aggregate is a mixture of basalt coarse aggregate and basalt fine aggregate in a ratio of 0.5-2:0.5-2; The particle size of the basalt coarse aggregate is 5 to 30 mm; the particle size of the basalt fine aggregate is 0.5 to 2 mm; The reinforcing fiber is at least one of basalt fiber, glass fiber, carbon fiber, polypropylene fiber, polyester fiber, polyethylene fiber, and polyacrylamide fiber; The mixed solution in step S2 is prepared by mixing anhydrous ethanol: water: ammonia monohydrate in a weight ratio of 4-6: 0.5-2: 0.5-2.

2. A process for processing high-bonding concrete as claimed in claim 1, characterized in that: The processing steps are as follows: Step 1, weighing each raw material according to weight, stirring and mixing basalt coarse aggregate, basalt fine aggregate, and blast furnace slag powder at 10-20 rpm for 30-50 minutes, and drying at 25-40° C. during the stirring and mixing process to obtain a mixture; Step 2: Put the mixture prepared in step 1 into a mixing tank, heat the modified asphalt to 150-180° C., add it evenly into the mixing tank within 20-30 seconds, stir for 1-3 hours at a stirring speed of 15-25 rpm, and obtain an asphalt mixture; Step 3, preheat the asphalt mixture prepared in step 2 and add it to the above-mentioned mixing tank together with basalt fiber, maintain the temperature in the mixing tank at 150-180°C, stir at a speed of 15-25rpm for 20-40min, then add lime and modified filler, stir and mix at a speed of 20-40rpm for 10-30min, control the discharge temperature at 160-170°C, and obtain high-adhesion concrete.

3. The processing technology of high-bonding concrete as claimed in claim 2, characterized in that: The steps include: Step 1, 50 kg of basalt coarse aggregate, 50 kg of basalt fine aggregate, and 20 kg of blast furnace slag powder were stirred and mixed at 15 rpm for 40 min, and dried at 30° C. during the stirring and mixing process to obtain a mixture; Step 2: put the mixture prepared in step 1 into a mixing tank, heat 80 kg of modified asphalt to 160° C., add it evenly into the mixing tank within 25 seconds, stir for 2 hours at a stirring speed of 20 rpm, and obtain an asphalt mixture; Step 3, preheat the asphalt mixture prepared in step 2 and add it together with 4 kg of basalt fiber into the above mixing tank, maintain the temperature in the mixing tank at 170°C, stir at a speed of 20 rpm for 30 min, then add 12 kg of lime and 20 kg of modified filler, stir and mix at a speed of 30 rpm for 15 min, control the discharge temperature at 165°C, and obtain high-cohesive concrete; The preparation method of the modified asphalt is as follows: 20 kg of asphalt was heated to 170°C, maleic anhydride grafted EVA particles with a mass fraction of 8% of asphalt and mineral oil with a mass fraction of 2% of asphalt were added, low-speed shear swelling was performed at a shear rate of 2000 r / min for 20 minutes, and then high-speed shear was performed at a shear rate of 4000 r / min for 60 minutes to obtain modified asphalt; The preparation method of the modified filler is as follows: S1. Add 1 kg of tris(3-triethoxysilylpropyl)isocyanate to 10 kg of diethylene glycol ethyl ether at 80° C. and 200 rpm under stirring, and continue stirring for 12 hours to obtain a modifier; S2. Add 20 kg of silicon powder to 100 kg of a mixed solution, wherein the mixed solution is prepared by mixing anhydrous ethanol, water and ammonia monohydrate in a weight ratio of 5:1:1, stir at 70°C and 200 rpm for 10 min, then ultrasonicate at 200 W for 10 min with an ultrasonic frequency of 60 kHz to obtain a dispersion, add 10 kg of the modifier prepared in step S1, stir at 200 rpm for 12 h, and dry at 70°C under a nitrogen flow until all the solvent evaporates to obtain a modified filler.

Citation Information

Patent Citations

  • Polymer modified asphalt and preparation method thereof

    CN101531817A

  • Plant-mixed hot regenerated asphalt concrete and preparation process thereof

    CN109626875A